Investigation of the application of an enzyme-based biodegradability test method to a municipal solid waste biodrying process - Wagland, Stuart T.; Godley, Andrew R.; Tyrrel, Sean F. (Elsevier, 2011)
This paper presents a study to evaluate the recently developed enzymatic hydrolysis test (EHT) through its repeated application to a waste treatment process. A single waste treatment facility, involving a biodrying process, has been monitored using three different methods to assess the biodegradable content of the organic waste fractions. These test methods were the anaerobic BMc, aerobic DR4 and the EHT, which is a method based on the enzymatic hydrolysis of the cellulosic content of waste materials. The input municipal solid waste (MSW) and the output solid recovered fuel (SRF) and organic fines streams were sampled over a period of nine months from a single mechanical biological treatment (MBT) facility. The EHT was applied to each stream following grinding to <10 mm and <2 mm, in order to investigate the effect of particle size on the release of dissolved organic carbon (DOC) from enzyme hydrolysis. The output organic fines were found to more biodegradable than the MSW input and SRF output samples in each of the test methods, significantly (p<0.05) for the EHT and DR4 methods, on the basis of DOC released and oxygen consumed respectively. The variation between sample replicates for the EHT was higher where sample sizes of <2 mm were analysed compared to sizes of <10 mm, and the DOC release at each phase of the EHT was observed to be higher when using particle sizes of <2 mm. Despite this, additional sample grinding from the <10 mm to a smaller particle size of <2 mm is not sufficiently beneficial to the analysis of organic waste fractions in the EHT method. Finally, it was concluded that as similar trends were observed for each test method, this trial confirms that EHT has the potential to be deployed as a practical operational biodegradability monitoring tool.